Science Process Skills and Critical Thinking in Science: Urban and Rural Disparity (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2020)
The study focuses on the relationship between process skills and critical thinking in junior high school students in learning science. Besides, an interrelation between process skill and critical thinking skills was also investigated. The study used a mixed-method. A sample of this study is 689 students of total sampling technique. Quantitative data were analyzed by SPSS 21 to find descriptive statistics in terms of mean, min, max while qualitative were analyzed in-depth interviews. The finding shows that the science process skill of students in learning science whether urban and rural areas are good categories. The independent sample t-test shows that students’ science process skills in learning science in urban tend to be higher than in rural schools (p0.01). Students’ critical thinking in learning science for urban areas is high but for rural areas is a fair category, with significance p0.001. The regression showed the level of contribution of students’ science process skill influence as much as 51.5% for critical thinking. The other research result was found that students’ science process skill affects critical thinking in learning science. Moreover, a comparison between students’ science process skills and critical thinking based on their school location showed that urban is higher than rural.